Poly(3, 4‐Propylenedioxythiophene) Capsulated Yolk–Shell Carbon Spheres for High‐Performance Electrochemical Capacitors. Issue 5 (5th August 2018) - Xiang, Ling; Ali, Ahmat; Jamal, Ruxangul; Ding, Shuai; Zhong, Ziping; Abdiryim, Tursun
Abstract : In this article, the yolk–shell structure of resin‐based carbon spheres (YRFC) and the solid structure of resin‐based carbon spheres (SRFC) were prepared by condensation polymerization, and then novel spherical composites of poly(3, 4‐propylenedioxythiophene)/YRFC (PProDOT/YRFC) and PProDOT/SRFC were obtained by in situ chemical oxidative polymerization. The prepared composites were characterized by Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible absorption spectra (UV–vis), Raman, X‐ray diffraction (XRD), Brunauer–Emmett–Teller (BET), X‐ray photoelectron spectrometer (XPS), scanning electron microscope (SEM), and transmission electron microscopy (TEM). Electrochemical behavior of the composites were investigated with reference to their suitability as electrode materials in electrochemical capacitors (ECs), which were accomplished by a combination of cyclic voltammetry and galvanostatic charge/discharge cycles. The resultant PProDOT/YRFC composite showed ideal charge storage capacity with a specific capacitance of 327.5 F g −1 at the current density of 1 A g −1, which is much higher than that of the materials of PProDOT/SRFC (298.1 F g −1 ) and PProDOT (180.9 F g −1 ). Furthermore, long cycle life was achieved with the optimized PProDOT/YRFC and the capacitance retention is 87.3% after 10, 000 charge/discharge processes, which was attributed to its uniformly dispersible fluffy structure. POLYM. COMPOS., 40:1989–1999, 2019. © 2018 Society of Plastics Engineers